Octenyl succinic anhydride starch and its polyelectrolyte complexes as stabilizers in Pickering emulsions - Nattawut Charoenthai; Kun Sodalee; Satit Puttipipatkhachorn (Faculty of Pharmacy, Mahidol University, 2022)
Pickering emulsions, also known as emulsions stabilized by solid particles, have been increasingly applied in pharmaceutical products due to their high stability and non-toxicity. Due to unwanted toxicity from low molecular weight surfactants used as emulsifiers in classical emulsions, solid particles of biopolymers have been used as stabilizers in Pickering emulsions. This review summarizes the recent research on using octenyl succinic anhydride (OSA) starch and its polyelectrolyte complexes as stabilizers in Pickering emulsions. OSA starch-based Pickering emulsion has been reported to prepare various dosage forms such as emulsion, nanoemulsion, microcapsules, nanocapsules, and redispersible dry emulsion. The information obtained indicates the increasing trend in the application and practical uses of Pickering emulsions in the pharmaceutical industry.